Improving Cloud Datacentre Scalability, Agility and Performance Using OpenFlow - Baker, C.; Anjum, A.; Hill, R.; Bessis, N.; Kiani, S. L. (2012 4th International Conference on Intelligent Networking and Collaborative Systems, 2012)
With network infrastructure reaching capacity limits, new ways of managing network traffic and devices in Cloud data centres need to be investigated to better scale and manage the data centre resources. Open Flow can be a good fit for the usage within a datacentre due to its promise to reduce the cost of operations by reducing the time needed to configure network resources and flexibly managing the operations. Open Flow allows a programmable Software Defined Network to be implemented and network resources such as switches can be remotely and collectively configured, controlled and monitored. With increasing number of resources in data centres, and by consequence the networking hardware and software, Open Flow can be used to manage the network devices and the flow of traffic throughout the network. This paper investigates if Open Flow based switches allow for flexible networking and administration to enable quick network segmentation, packet re-routing, permit scalability and allow for quick network setup in Cloud data centres. With the help of experiments, this work also investigates what design and implementation considerations need to be made to achieve scalability, agility and performance in Cloud data centres.